The legal regulation of internal party democracy - a study of South Africa and Germany - Maier, Benjamin Gerhard (Department of Public Law, 2015)
This paper attempts to expand the knowledge on these issues and therefore seeks to get a deeper understanding on the legal regulation of internal party democracy, which is widely considered as one of the most controversial topics concerning party regulation. This will be done by carrying out a case study of two constitutional democracies that handle party regulation differently. Germany, known as 'heart land of party law', constitutes the example of a state in which the internal organisation and functioning of political parties is regulated by both the Basic Law (the German Constitution) and federal laws. South Africa will be provided as the contrast example of a state that lacks express provisions that regulate the internal organisation and functioning of political parties. This paper does therefore not seek to conduct a 'classical' comparative study as the legal framework of two countries will be examined which deal in different ways with internal party democracy. However, this research approach promises to create a more holistic - even though certainly not complete - image of the challenges of the legal regulation of internal party democracy.